On modelling and control design for self-balanced two-wheel vehicle - Quang, Nguyen Hoang (Vietnam Journal of Mechanics, 2008)
In this paper, the modeling and control design of a self-balancing mobile robot are presented. The method of sub-structures is employed to derive the differential equations of motion of the robot. Based on the linearized equations of motion, a controller is designed to maintain a stable motion of the robot. Some numerical simulation results are shown to clarify the designed controller.